Validity of low-magnification narrow-band imaging in annual endoscopy screening for gastric neoplasms: A case-control study - Ryuichi Nagashima (Gastroenterology & Endoscopy, 2023)
Previously, I have reported the efficacy of whole stomach observation using magnifying narrow-band imaging at low magnification (LM-NBI) after routine white-light imaging (WLI). LM-NBI can detect lesions overlooked by WLI. However, the effectiveness of annual examinations remains unexplored. I conducted this case-control study at a single institution. In LM-NBI group, patients with chronic gastritis underwent a LM-NBI scan, defined as the minimal magnification offering maximal visual field coverage to unveil to the microsurface pattern of gastric mucosa, of the whole stomach following WLI. Historical control was used as the conventional magnifying endoscopy (CE) group. In both groups, index endoscopy, which equalizes the status, was performed first, and subsequently annually endoscopies up to five times were conducted. The first annual examination was performed from April 2019 to March 2020 in LM-NBI group and from April 2015 to March 2016 in CE group. The detection of gastric neoplasia was analyzed according to medical records. Among 388 patients in the LM-NBI group, and 381 in the CE group, 15 and 5 patients with gastric neoplasia were respectively identified. Except for one mucosa-associated lymphoid tissue lymphoma, all were epithelial neoplasias. All endoscopic examinations were performed safely without complications which needed additional medical interventions. Through a Cox proportional hazards model, the hazard ratio of 2.78 (95% CE, 1.01–7.64) was determined. Kaplan–Meier analysis (p ​= ​0.039, log-rank test) revealed superior efficacy of annual LM-NBI over CE in detecting gastric neoplasia. This is the first study to report the efficacy of annual endoscopy using LM-NBI.